Tháng Sáu 9, 2023

Rút gọn biểu thức \(B=(x-2)\left( {{x}^{2}}+2x+4 \right)-x\left( x-1 \right)\left( x+1 \right)+3x\)

Rút gọn biểu thức \(B=(x-2)\left( {{x}^{2}}+2x+4 \right)-x\left( x-1 \right)\left( x+1 \right)+3x\)

A. \(x-8\)

B. \(8-4x\)

C. \(8-x\)

D. \(4x-8\)

Hướng dẫn Chọn đáp án là: D

Lời giải chi tiết:

\(\begin{array}{l}B = \left( {x – 2} \right)\left( {{x^2} + 2x + 4} \right) – x\left( {x – 1} \right)\left( {x + 1} \right) + 3x\\B = \left( {x – 2} \right)\left( {{x^2} + x.2 + {2^2}} \right) – x\left( {{x^2} – 1} \right) + 3x\\B = {x^3} – {2^3} – x.{x^2} + x.1 + 3x\\B = {x^3} – 8 – {x^3} + x + 3x\\B = 4x – 8\end{array}\)

Chọn D.